Photocatalytic degradation mechanisms of dimethyl phthalate esters by MWCNTs-anatase TiO2 nanocomposites using the UHPLC/Orbitrap/MS technique - Tong, Ling Tan; Kian, Mun Lee; Chin, Wei Lai; Sok, Lai Hong; Abdul Rashid, Suraya (Elsevier BV, 2020)
Dimethyl phthalate esters (DMPEs) have been identified as endocrine disrupting plastisizers and emerging contaminants which can be released readily upon exposure to the environment. In this study, MWCNTs/TiO2 nanocomposites, which possess the potential application for the photocatalytic degradation of DMPEs under UV irradiation, were prepared via simple one-pot sol-gel reaction using titanium isopropoxide (TTIP) as titania precursor and multiwalled carbon nanotubes (MWCNTs). The MWCNTs/TiO2 nanocomposites was calcined in air for 2 h at the temperatures ranging from 350 to 750 °C. As a result, the MWCNTs/TiO2 nanocomposites synthesized at calcination temperature of 450 °C demonstrated the highest photodegradation efficiency of 97% after 180 min UV irradiation and its degraded products were evaluated using the ultra high performance liquid chromatography (UHPLC) coupled with a high resolution (HR) Orbitrap mass spectrometry (MS). A primary degradation mechanism was proposed and it was noteworthy that some new intermediates were discovered and reported. This work has developed a simple method for qualitative determination of DMPEs based on HPLC with UV detection.